(untitled) (Journal of Human Sciences, 2024)
The work of Jean-Marie Gustave Le Clézio, a prominent French writer and Nobel laureate in literature in 2008, is deeply rooted in geography. Places occupy a central role in his writings, almost becoming full-fledged characters themselves, and significantly contribute to the richness of his narratives. Through his novels, short stories, and essays, Le Clézio explores a vast array of landscapes, cultures, and spaces, thus offering readers a literary experience that transcends geographical boundaries. This exploration of places is intimately linked to his reflections on identities, migrations, intercultural encounters, and quests for meaning, making geography an essential element of his artistic vision. In this introduction, we will delve into the fascinating geographical universe of Le Clézio’s work, exploring the different places that shape his writing and highlighting how these settings reflect profound and universal themes.